Acute and Chronic Pancreatitis - Rodrigo, Luis (IntechOpen, 2015)
The inflammatory procceses of pancreatic gland can be acute and chronic. Acute pancreatitis constitutes the majority of cases requiring hospital admission in gastroenterology. We are yet to discover many things about its pathophysiology, which is a certain drawback for the progress in its treatment. Prediction of severity is necessary for the management plan. However, our progress in the field was significant in the recent decade and a leap forward is expected in this cumbersome condition which has many unmet needs. Chronic pancreatitis is a progressive inflammatory disease characterized by debilitating pain and pancreatic insufficiency. Although medical treatment and endoscopic interventions are primarily offered to patients with chronic pancreatitis, approximately around 50% will ultimately require palliative surgery.